Rupture of the internal jugular vein and tension pneumothorax in a penetrating neck-lung injury due to iron splinters: a case report - Brilliant, Brilliant; Sabri, Muhammad; Fadilla, Annisa Tria; Hatta, Hariadi (Universitas Muhammadiyah Purwokerto, 2024)
Background: Penetrating neck injuries are relatively rare but pose significant challenges due to the concentration of vital structures in this area. This case report presents a unique in-stance of a 20-year-old male with a penetrating neck injury caused by iron splinters, resulting in the rupture of the internal jugular vein and tension pneumothorax.Case Presentation: The patient, a 20-year-old male, presented with restlessness, chest pain, rapid breathing, and a penetrating wound on the left side of the neck. Initial management included needle decompression for tension pneumothorax and radiological assessments to localize the foreign body. C-arm revealed that the foreign body had penetrated the upper left thoracic region and lung parenchyma. The surgical intervention involved repairing the internal jugular vein and performing pulmonary resection to remove the iron splinters.Conclusions: This case highlights the importance of a multidisciplinary approach in managing complex penetrating neck injuries. Advanced imaging techniques and timely surgical interventions are crucial for optimizing patient outcomes. Future research should focus on refining diagnostic protocols and exploring minimally invasive surgical techniques to improve the management of such injuries.